2011
DOI: 10.15809/irriga.2011v16n1p42
|View full text |Cite
|
Sign up to set email alerts
|

Germinação E Vigor De Sementes De Crambe Sob Estresse Hídrico

Abstract: RESUMOO presente trabalho teve por objetivo avaliar a germinação e o vigor de sementes de crambe, sob condições de estresse hídrico induzidas por soluções de polietileno glicol. As sementes foram colocadas para germinar em substrato embebido com soluções de polietileno glicol, utilizando-se os potenciais osmóticos de 0 (controle), -0,2; -0,4; -0.6; -0.8; -1,0; -1,2 e -1,4MPa. Avaliou-se a germinação das sementes pela porcentagem de plântulas normais e porcentagem de emissão de raiz primária, e o vigor pelo tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
(5 reference statements)
1
7
0
3
Order By: Relevance
“…These results corroborate those found by Teixeira et al (2011), who observed that the reduction in the osmotic potential of the soaking solution caused decreases in the germination of crambe seeds. Medeiros et al (2015) also observed significant reduction in the germination of sesame seeds from the water potential of -0.2 MPa on, reaching null values at the osmotic potential of -1.0 MPa.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results corroborate those found by Teixeira et al (2011), who observed that the reduction in the osmotic potential of the soaking solution caused decreases in the germination of crambe seeds. Medeiros et al (2015) also observed significant reduction in the germination of sesame seeds from the water potential of -0.2 MPa on, reaching null values at the osmotic potential of -1.0 MPa.…”
Section: Resultssupporting
confidence: 92%
“…Teixeira et al (2011) also found values close to zero in the germination of crambe seeds at osmotic potentials lower than -1.0 MPa induced by PEG 6000. For canola, Santos et al (2012) observed that the reduction of water availability in the substrate from -0.3 MPa on significantly reduced seed germination.…”
Section: Resultsmentioning
confidence: 59%
“…However, no records exist regarding the physiological performance of FMS CR1101 lineage under low water availability in Brazil. In general, studies with crambe are focused on seed storage, germination, and oil quality (Martins et al, 2011;Teixeira et al, 2011). The knowledge about the physiological performance of a specific genotype submitted to water stress give us the base to expand the culture to regions characterized by low precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Originário da região quente e seca da Etiópia foi domesticado na região fria e seca do Mediterrâneo encontrando-se relatos que atestam tolerância das plantas a períodos de estresse hídrico (Teixeira et al, 2011).…”
Section: Introductionunclassified